DIVERSIFIKASI HASIL PERTANIAN TERINTEGRASI DAN PENDAPATAN PETANI PETERNAK DI DESA KERTA KECAMATAN PAYANGAN KABUPATEN GIANYAR - Widhyawaty, Ni Putu (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol 7 No 2 (2019): OKTOBER 2019DO - 10.24843/JMA.2019.v07.i02.p07, 2019)
The successful diversification of product yields is the main characteristic of integrated agriculture. Diversified farming in order to obtain optimal results requires management that is more comprehensive. The purpose of this study was to find out the main and side yields, the quality of the product, the level of food diversification, and the income level of simantri and non-simantri farmers in Kerta Village, Payangan Sub-District, Gianyar Regency. The study was designed as a quantitative descriptive study through survey activities in Kerta Village, Payangan Sub-district, Gianyar Regency for one year by taking samples of farmers who implemented simantri and non-simantri. The main products of farmers in Kerta Village are citrus fruits, guava, mangosteen, durian, heliconia, and banana leaves and livestock products including meat, calves, and chicken eggs. The by-products are biogas, biourine and compost with better quality because they are carried out according to the procedure so that the amount of pathogenic bacteria can be reduced in number to reduce water, air and soil pollution. Diversification of integrated agricultural products in Kerta Village is carried out by processing manure into biogas and bio urine that provide economic benefits to farmers, especially as production facilities in the form of compost and liquid fertilizer used by farmers to improve soil fertility. In general, the income of farmers in integrated farming systems (simantri) in Kerta village is increasing, because in addition to obtaining yields from agriculture and plantations, it is also from livestock, which actually increases their income from the results of animal husbandry processing.